1998
DOI: 10.1002/(sici)1097-0010(199811)78:3<297::aid-jsfa117>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sulphur dioxide and must extraction on colour, phenolic composition and sensory quality of red table wine

Abstract: Red wines were made during 1992 from Vitis vinifera var Roriz grapes using a high and a low level of extraction and three levels of total sulphur dioxide (0, 75 and 150 mg SO2 kg−1). From this single experiment, the effects of total SO2 and extraction on anthocyanin composition and colour were observed by HPLC, spectrophotometry and tristimulus colorimetry. High extraction produced a wine with more total pigments and total phenols than low extraction and increased the amount of organic acids extracted during f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(17 citation statements)
references
References 3 publications
2
12
0
1
Order By: Relevance
“…The disappearance of total monomeric pigments could be modelled by first‐order kinetics (Table 3), confirming the results of Bakker et al 30 Bakker27 reported a comparable value of k of −0.083 week −1 and later29 showed a range of k values of 0.053–0.108 week −1 for the loss of monomeric pigments in port wine allowed to mature normally. The k values were smaller in the presence than in the absence of pyruvic acid, and good correlation coefficients ( r 2 ) for all wine solutions were obtained (Table 3), explained by the formation of new monomeric anthocyanins (vitisin A‐type compounds) during storage.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…The disappearance of total monomeric pigments could be modelled by first‐order kinetics (Table 3), confirming the results of Bakker et al 30 Bakker27 reported a comparable value of k of −0.083 week −1 and later29 showed a range of k values of 0.053–0.108 week −1 for the loss of monomeric pigments in port wine allowed to mature normally. The k values were smaller in the presence than in the absence of pyruvic acid, and good correlation coefficients ( r 2 ) for all wine solutions were obtained (Table 3), explained by the formation of new monomeric anthocyanins (vitisin A‐type compounds) during storage.…”
Section: Resultssupporting
confidence: 83%
“…During the course of the experiment the concentrations of malvidin 3‐glucoside, malvidin 3‐acetylglucoside and malvidin 3‐ p ‐coumarylglucoside decreased, and these anthocyanin losses could be modelled by first‐order kinetics, in agreement with previous reports 27. 29, 30 The presence of pyruvic acid in the wines did not affect the order of the reaction, confirming the findings in model wine solutions by Romero and Bakker 23–25…”
Section: Resultssupporting
confidence: 79%
“…This was especially noticeable in the wines made with the high sulfur dioxide concentrations. Sulfur dioxide has been shown not to influence vitisin A degradation (Bakker et al 1998) and it is therefore concluded that it is the production of vitisin A that determines its concentration in wine. The limiting factor determining vitisin A synthesis at high sulfur dioxide concentrations may be an insufficient concentration of suitable oxidant.…”
Section: Effect Of Sulfur Dioxide On the Formation Of Vitisin A Durinmentioning
confidence: 99%
“…Both anthocyanins originating from grape skins and polymeric pigments contribute to wine color. This decrease is due to either reabsorption on to the grape skins or yeast cell walls, or as a result of polymerization reactions and the formation of polymeric pigments (Bakker et al, 1998;Gao et al, 1997). Several studies have shown that anthocyanin extraction reaches a maximum early on during fermentation followed by a decrease (Nagel and Wulf, 1979;Gao et al, 1997;Reichwage, 2012).…”
Section: Antioxidants In Red Wine During Alcoholic Fermentationmentioning
confidence: 99%